Blinded by the whites : why race still matters in 21st-century America - Ikard, David, 1972- (Blacks in the diaspora., 2013)
The scholar and author posits that the election of Barack Obama gave political currency to the (white) idea that Americans live in a post-racial society. But the persistence of racial profiling, economic inequality between Blacks and whites, disproportionate numbers of Black prisoners, and disparities in health and access to healthcare suggest there is more to the story. -- Description from dust jacket flap.